Optimum Operating Conditions of (PbxX1−x)(ZryTizY1−y−z) Piezoelectric Transducer for Vibrational Energy Harvesting Applications - Funda Demir; Mustafa Anutgan (Shock and Vibration)
The electrical energy production capability of bimorph (PbxX1-x)(ZryTizY1-y-z) fiber composite piezoelectric transducer has been investigated for energy harvesting applications. The material has been analyzed under different frequencies, bending amounts, and temperatures. The operating conditions for maximum electrical energy outcome have been determined. The natural frequencies of oscillations in the macro dimensions have been found to be inversely proportional to the length of the material. On the other hand, the voltage output with respect to the oscillation frequency exhibits an interesting behavior such that the characteristic curve shifts to higher frequencies as the bending radius is decreased. This behavior has been interpreted as a result of possible overtone transitions of the oscillations to a stiffer mode. The increasing temperature has been observed to have a negative effect on the piezoelectric energy harvesting property. When the determined optimum conditions were utilized, the amount of electrical energy stored in 6300 s by an energy harvester circuitry has been found to be 0.8 J.